Space, transformation and the negotiation of Neopalatial society: the mutability of the pier-and-door partition in its social context - Rapakko, Jonas (Journal of Greek Archaeology, 2025)
The pier-and-door partition was a Minoan architectural invention, a wall consisting of a series of openings (or doorways) that could be opened or closed in different combinations by the use of the wooden door leaves of the structure. The doorways of the structure were closable by double door leaves, which were attached to the door jambs of the structure. Pier-and-door partitions were most frequently used in polythyron (pl. polythyra) halls in Minoan buildings. Polythyron halls usually had two or three walls (sometimes only one, but this is rather rare) consisting of pier-anddoor partitions, with the rest of the walls solid without openings. The hall could be transformed from an open hall (with all doors open), to a room with access to other rooms (with an open door in some or each of the walls), and to a completely closed space (with all doors closed). The pier-anddoor partitions were most commonly used in Minoan Halls, a hall system consisting of a polythyron, a forehall and a light well. Whereas the terms pier-and-door partition hall, polythyron hall and Minoan Hall have been used somewhat interchangeably, actual Minoan Halls would have consisted of these aforementioned elements; for the sake of clarity, in this paper the term Minoan Hall is reserved for these halls commonly assigned as ones, while other pier-and-door partition halls without these elements are termed simply as pier-and-door partition halls, or polythyron halls. The terms pier-and-door partition hall and polythyron hall are thus used to denote all spaces with pier-and- door partitions, regardless whether they were Minoan Halls or other types of polythyron halls.